Leading with Emotional Intelligence / Nurulizzah Mohamed - Mohamed, Nurulizzah (2003)
It is possible for anybody to feel hurt, mad, destructive or resentful, towards something or someone without really knowing it. What is worse, we can take out how we feel about one person on another. That is something nobody really wants to do. But the knot can be undone, if we know how to cope with our feelings, which describes Emotional Intelligence. Emotional Intelligence is an important aspect of all human interaction. According to a recent research, effective leaders have a high level of Emotional Intelligence, which distinguishes them in every field. High IQ, advanced degrees or technical expertise are not the only elements which portray good leaders. When leaders or managers understand their reactions and interactions with others, they can express the sensitivity and guidance as true leaders. Self awareness, self confidence and self control are the examples of competencies which are at a premium in today's job market. Effective leaders should have good commitment and integrity, able to communicate, influence, and initiate, and willing to accept change. The higher up the leadership ladder you go, the more vital these skills become.